Preparação de derivados de β-glicosidase por imobilização em suportes sólidos derivatizados - Borges, Diogo Gontijo (2011)
B-glucosidase (BG) is an important enzyme for several biotechnological applications. This enzyme plays an important role in hydrolyses of lignocellulosic biomass in order to produce second generation ethanol (2G ethanol). The enzimatic hydrolysis of cellulose requires the sinergystic action of endoglucanases, exoglucanases and β-glucosidases. Endo e exoglucanases are strongly inhibited by cellobiose and its accumulation into reaction medium decreases the hydrolysis rate. The supplementation of the reaction medium with BG can reduce the inhibition effect, leading to higher conversions of cellulose to glucose. In this work, BG was immobilized on different solid supports in order to obtain an active and stable derivative to be used in hydrolyses of sugarcane bagasse. BG was immobilized on glyoxyl-agarose (GA) and polyacrylic matrix (MP) at 25oC and pH 9.0 and 4.8, respectively. To improve the immobilization yield on glyoxyl-agarose at pH 9.0, a chemical amination of the enzyme surface was required. However, BG was inactivated during the immobilization reaction due to alkaline conditions that are required to immobilize enzymes on glyoxylagarose support. Nevertheless, the presence of a competitive inhibitor (glucose) during immobilization of BG preserved about 70% of the initial activity. However, the reduction step with sodium borohydride (end point of the reaction) drastically reduced the derivative activity even in the presence of glucose. The BG immobilization in presence of competitive inhibitor allowed the preparation of a derivative approximately 4 times more active than one prepared in inhibitor absence. On the other hand, the best derivative was prepared adsorbing the enzyme on polyacrylic resin covered with carboxylic groups. After four hours of reaction, the immobilization yield and the recovered activity were ca. 71% and 97%, respectively. Pretreated sugarcane bagasse (10% w/v, dry basis) was hydrolyzed at 50oC, pH 4.8 (50 mM sodium citrate buffer), for 24 h, using soluble cellulase (Acellerase 1500) in the enzyme/substrate ratio of 20 FPU/gcellulose. Hydrolyses under same conditions were performed by supplementing the reaction medium with BG immobilized on glyoxyl-agarose (BG-GA) or BG immobilized on polyacrylic resin (GA-MP) in the enzyme/substrate ratio of 120 U/gcellulose. Five batches were performed under - xi - conditions described above by reusing the immobilized BG and non-converted cellulose after thoroughly washing with distilled water. The supplementation of the reaction medium with immobilized BG enhanced the cellulose conversions in all batches. This behavior is due to the fact that BG removes cellobiose from the reaction medium, avoiding its accumulation, which could inhibit the endoglucanases and exoglucanases. However, a decrease of the cellulose conversion after the second batch was observed (cellulose conversion decreased from ca. 50% to 15-25%). Anyway, this work shows that supplementation of the commercial enzymatic complexes with immobilized BG is advantagous. However, the stabilization of the immobilized BG is still required.